Perioperative management for invasive brain–computer interface implantation under surgical navigation in a patient with traumatic spinal cord injury: a case report - Shuhui Yang; Qiang Sun; Hong Mo; Wenyao Cui (Frontiers in Human Neuroscience, 2026)
Background The clinical application of invasive brain–computer interface combined with surgical navigation in patients with traumatic spinal cord injury remains limited, and there is a lack of a standardized perioperative nursing cooperation strategy. This paper summarized the intraoperative cooperation and nursing experience from a single case, aim to provide a reference for clinical practice. Case summary Preoperatively, the patient presented with a muscle strength of grade 4 in both forearms and upper arms, and grade 0 in both hands. Surgical navigation-assisted invasive brain–computer interface implantation was planned. The operation was successfully completed, and device activation was performed on August 13, 2025. At the 6-month follow-up, an assessment using the Upper Extremity Motor Score indicated that the patient achieved a grip score of 6 points for the left hand and 4 points for the right hand, with total scores of 11 points for the left hand and 8 points for the right hand, respectively. Improvement in bilateral upper limb motor function was observed. The patient regained voluntary motor function, and the complete paralysis was alleviated. No adverse events occurred during the hospitalization and follow-up period, and the patient and his family members reported a high level of satisfaction. Conclusion This paper summarized the perioperative care experience of a patient with traumatic spinal cord injury who underwent an invasive brain–computer interface implantation under surgical navigation. During the perioperative period, refined nursing cooperation was implemented through establishing a multidisciplinary team, conducting comprehensive preoperative preparations, precisely coordinating with surgical navigation, strictly preventing surgical site infections, standardizing postoperative monitoring, and enhancing post-discharge follow-up. The precise perioperative nursing plan is scientifically sound and clinically feasible, providing a practical foundation for the future implementation of perioperative nursing strategies for similar surgical procedures.